Surgical treatment of respiratory tuberculosis patients in the Siberian and Far Eastern Federal Districts during the initial period of the COVID-19 pandemic - N. G. Grischenko; D. V. Krasnov; S. L. Naryshkina; D. A. Skvortsov (Туберкулез и болезни лёгких)
The objective: to analyze the quality of phthisiosurgical care in the Siberian and Far Eastern Federal Districts monitored by Novosibirsk Tuberculosis Research Institute (NTRI).Subjects and Methods. Statistical reports for 2019 from phthisiosurgical departments of 17 Russian regions within the Siberian and Far Eastern Federal Districts were analyzed. The reports refl ected the initial period of the pandemic.Results. The analysis of the quality of phthisiosurgical care in the Siberian and Far Eastern Federal Districts covered the areas monitored by Novosibirsk Tuberculosis Research Institute, the Russian Ministry of Health. The main performance rates of phthisiosurgical departments of 17 Russian regions are presented for 2019, they demonstrate a positive trend, and their facilities and resources have signifi cantly improved. The trend towards reduction of phthisiosurgical beds is observed in the regions, which may be due to the service centralization and improved access to surgical and high-tech care in federal institutions. Surgical departments possesses substantial reserves for increasing the number of surgeries, one of which is the revision of cohorts.